Prognostic factors for overall survival after surgical resection in patients with thymic epithelial tumors: A systematic review and meta-analysis. Issue 39 (30th September 2022) - Li, Jiaduo; Liu, Yaling; Zhang, Xiaohe; Zheng, Xuguang; Qi, Guoyan
Abstract : Background: Thymic epithelial tumors (TETs) originate in the thymic epithelial cell, including thymoma and thymic carcinoma. Surgical resection is the first choice for most patients. However, some studies have shown that the factors affecting the prognosis of these patients are not consistent. To evaluate prognostic factors in patients with surgically resected thymic epithelial tumors, we performed a meta-analysis. Methods: We searched the Chinese biomedical literature database, Pubmed, Embase, Cochrane Library and other electronic databases. Studies including postoperative overall survival (OS) and predictors of TETs were included. We made a comprehensive analysis the hazard ratios (HRs) through a single proportional combination. HRs were combined using single proportion combinations. Results: The meta-analysis included 11, 695 patients from 26 studies. The pooled OS was 84% at 5 years and 73% at 10 years after TETs operation. The age as continuous-year (HR 1.04, 95% confidence interval (CI) 1.02–1.04), incomplete resection (HR 4.41, 95% CI 3.32–5.85), WHO histologic classification (B2/B3 vs A/AB/B1 HR 2.76, 95% CI 1.25–6.21), Masaoka Stage (stage III/IV vs I/II HR 2.74, 95% CI 2.12–3.55, ) were the poor prognostic factors. Conclusions: For patients with TETs after surgical resection, advanced age, incomplete resection, WHO classification B2/B3, and higher Masaoka stage are risk factors for poor prognosis.